Implementasi Pembelajaran IPS Sebagai Penguatan Pendidikan Karakter di Sekolah Dasar - Erwin Simon Paulus Olak Wuwur; Oktaviani Adhi Suciptaningsih (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This study aims to analyze the implementation of social studies learning as strengthening character education in elementary schools. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The research subjects were social studies teachers and sixth grade students at an elementary school in Manggarai Regency. The results of the study show that social studies teachers have implemented character education in social studies learning through various activities, such as discussions, questions and answers, presentations, and educational games. The implementation of character education is also seen in students' attitudes and behavior, such as discipline, self-confidence, and social awareness. The obstacles encountered in the implementation of character education are the teacher's lack of understanding of the concepts and goals of character education, limited learning time, and limited resources and facilities. The school is trying to overcome these obstacles, such as increasing teachers' understanding of character education, using technology in learning, and collaboration between schools and communities in strengthening character education in elementary schools. Keywords: Implementation, Social Studies Learning, Character education This study aims to analyze the implementation of social studies learning as strengthening character education in elementary schools. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The research subjects were social studies teachers and sixth grade students at an elementary school in Manggarai Regency. The results of the study show that social studies teachers have implemented character education in social studies learning through various activities, such as discussions, questions and answers, presentations, and educational games. The implementation of character education is also seen in students' attitudes and behavior, such as discipline, self-confidence, and social awareness. The obstacles encountered in the implementation of character education are the teacher's lack of understanding of the concepts and goals of character education, limited learning time, and limited resources and facilities. The school is trying to overcome these obstacles, such as increasing teachers' understanding of character education, using technology in learning, and collaboration between schools and communities in strengthening character education in elementary schools. Keywords: Implementation, Social Studies Learning, Character education This study aims to analyze the implementation of social studies learning as strengthening character education in elementary schools. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The research subjects were social studies teachers and sixth grade students at an elementary school in Manggarai Regency. The results of the study show that social studies teachers have implemented character education in social studies learning through various activities, such as discussions, questions and answers, presentations, and educational games. The implementation of character education is also seen in students' attitudes and behavior, such as discipline, self-confidence, and social awareness. The obstacles encountered in the implementation of character education are the teacher's lack of understanding of the concepts and goals of character education, limited learning time, and limited resources and facilities. The school is trying to overcome these obstacles, such as increasing teachers' understanding of character education, using technology in learning, and collaboration between schools and communities in strengthening character education in elementary schools. Keywords: Implementation, Social Studies Learning, Character education This study aims to analyze the implementation of social studies learning as strengthening character education in elementary schools. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The research subjects were social studies teachers and sixth grade students at an elementary school in Manggarai Regency. The results of the study show that social studies teachers have implemented character education in social studies learning through various activities, such as discussions, questions and answers, presentations, and educational games. The implementation of character education is also seen in students' attitudes and behavior, such as discipline, self-confidence, and social awareness. The obstacles encountered in the implementation of character education are the teacher's lack of understanding of the concepts and goals of character education, limited learning time, and limited resources and facilities. The school is trying to overcome these obstacles, such as increasing teachers' understanding of character education, using technology in learning, and collaboration between schools and communities in strengthening character education in elementary schools. Keywords: Implementation, Social Studies Learning, Character education This study aims to analyze the implementation of social studies learning as strengthening character education in elementary schools. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The research subjects were social studies teachers and sixth grade students at an elementary school in Manggarai Regency. The results of the study show that social studies teachers have implemented character education in social studies learning through various activities, such as discussions, questions and answers, presentations, and educational games. The implementation of character education is also seen in students' attitudes and behavior, such as discipline, self-confidence, and social awareness. The obstacles encountered in the implementation of character education are the teacher's lack of understanding of the concepts and goals of character education, limited learning time, and limited resources and facilities. The school is trying to overcome these obstacles, such as increasing teachers' understanding of character education, using technology in learning, and collaboration between schools and communities in strengthening character education in elementary schools. Keywords: Implementation, Social Studies Learning, Character education This study aims to analyze the implementation of social studies learning as strengthening character education in elementary schools. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The research subjects were social studies teachers and sixth grade students at an elementary school in Manggarai Regency. The results of the study show that social studies teachers have implemented character education in social studies learning through various activities, such as discussions, questions and answers, presentations, and educational games. The implementation of character education is also seen in students' attitudes and behavior, such as discipline, self-confidence, and social awareness. The obstacles encountered in the implementation of character education are the teacher's lack of understanding of the concepts and goals of character education, limited learning time, and limited resources and facilities. The school is trying to overcome these obstacles, such as increasing teachers' understanding of character education, using technology in learning, and collaboration between schools and communities in strengthening character education in elementary schools. Keywords: Implementation, Social Studies Learning, Character education This study aims to analyze the implementation of social studies learning as strengthening character education in elementary schools. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. The research subjects were social studies teachers and sixth grade students at an elementary school in Manggarai Regency. The results of the study show that social studies teachers have implemented character education in social studies learning through various activities, such as discussions, questions and answers, presentations, and educational games. The implementation of character education is also seen in students' attitudes and behavior, such as discipline, self-confidence, and social awareness. The obstacles encountered in the implementation of character education are the teacher's lack of understanding of the concepts and goals of character education, limited learning time, and limited resources and facilities. The school is trying to overcome these obstacles, such as increasing teachers' understanding of character education, using technology in learning, and collaboration between schools and communities in strengthening character education in elementary schools.